DESIGNING UI/UX FOR ELEMENTARY SCHOOL E-LEARNING USING DESIGN THINKING METHOD - Muhammad Rifqi Anshari; Adam Prayogo Kuncoro; Pungkas Subarkah (STMIK Royal, 2024)
Abstract: Advances in technology and the internet have an impact on various daily activities, including the teaching and learning process. E-learning facilitates flexible learning without being constrained by space and time constraints. With e-learning, subject matter can be delivered consistently and more standardly than conventional learning which depends on the conditions of the teacher or instructor. One school in Banjarnegara Regency faced problems with students who had difficulty in learning, especially English. The learning media owned is limited to package books only. Therefore, schools need to have media that can support the learning process to be more optimal. This study aims to design and test UI/UX e-learning designs that suit the needs of the school using the design thinking method. This UI/UX design is expected to be an effective solution to overcome the limitations of learning media and improve the quality of student learning. Before the UI/UX design is implemented into the system, this study also conducts testing of the UI/UX design to assess its feasibility. Testing using the SUS (System Usability Scale) method resulted in a value of 82 with grade B, so it can be concluded that the design developed in this study is feasible to be deployed into the system and further developed. Keywords: E-learning; design thinking; system usability scale; UI/UX Abstrak: Kemajuan teknologi dan internet berdampak pada berbagai aktivitas sehari-hari, termasuk proses belajar-mengajar. E-learning memfasilitasi pembelajaran yang fleksibel tanpa terkendala oleh batasan ruang dan waktu. Dengan e-learning, materi pelajaran dapat disampaikan secara konsisten dan lebih standar dibandingkan pembelajaran konvensional yang bergantung pada kondisi guru atau instruktur. Salah satu sekolah di Kabupaten Banjarnegara menghadapi permasalahan dengan peserta didik yang kesulitan dalam pembelajaran, khususnya bahasa Inggris. Media pembelajaran yang dimiliki terbatas hanya pada buku paket saja. Oleh karena itu, sekolah perlu memiliki media yang dapat menunjang proses pembelajaran agar lebih optimal. Penelitian ini bertujuan untuk merancang dan menguji desain UI/UX e-learning yang sesuai dengan kebutuhan sekolah tersebut menggunakan metode design thinking. Desain UI/UX ini diharapkan dapat menjadi solusi efektif untuk mengatasi keterbatasan media pembelajaran dan meningkatkan kualitas belajar siswa. Sebelum desain UI/UX diterapkan ke dalam sistem, penelitian ini juga melakukan pengujian terhadap desain UI/UX untuk menilai kelayakannya. Pengujian menggunakan metode SUS (System Usability Scale) menghasilkan nilai 82 dengan grade B, sehingga dapat disimpulkan bahwa desain yang dikembangkan dalam penelitian ini layak untuk dideploy ke dalam sistem dan dikembangkan lebih lanjut. Kata kunci: E-learning; design thinking; system usability scale; UI/UX